2013
DOI: 10.1016/j.jpsychires.2013.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies of maximum number of drinks

Abstract: Maximum number of drinks (MaxDrinks) defined as “Maximum number of alcoholic drinks consumed in a 24-hour period” is an intermediate phenotype that is closely related to alcohol dependence (AD). Family, twin and adoption studies have shown that the heritability of MaxDrinks is approximately 0.5. We conducted the first genome-wide association (GWA) study and meta-analysis of MaxDrinks as a continuous phenotype. 1059 individuals were from the Collaborative Study on the Genetics of Alcoholism (COGA) sample and 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 42 publications
1
26
1
1
Order By: Relevance
“…It is unknown how K V 2.1 channels and its modifiers influence excitability of accumbens neurons or if ethanol dependence affects their function or expression in the PFC or NAc. However, intriguing evidence from a meta-analysis using samples from the Collaborative Study on the Genetics of Alcoholism (COGA) and the Study of Addiction: Genetics and Environment (SAGE) revealed that two SNPs in KCNB1 (rs2128158 and rs2929567) showed significant associations with maximum number of alcoholic drinks consumed in a 24 hr period (Pan et al, 2013). Given these converging lines of evidence, future studies should determine if ethanol-induced dysregulation of or genetic polymorphisms in K V 2.1 channels and their modifiers/silencers impact risk for developing an alcohol use disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unknown how K V 2.1 channels and its modifiers influence excitability of accumbens neurons or if ethanol dependence affects their function or expression in the PFC or NAc. However, intriguing evidence from a meta-analysis using samples from the Collaborative Study on the Genetics of Alcoholism (COGA) and the Study of Addiction: Genetics and Environment (SAGE) revealed that two SNPs in KCNB1 (rs2128158 and rs2929567) showed significant associations with maximum number of alcoholic drinks consumed in a 24 hr period (Pan et al, 2013). Given these converging lines of evidence, future studies should determine if ethanol-induced dysregulation of or genetic polymorphisms in K V 2.1 channels and their modifiers/silencers impact risk for developing an alcohol use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals with SNPs in OPRM1 , HTR3A/B , or GRIK1 genes moderate the reduction in heavy drinking by naltrexone, ondansetron, and topiramate treatment, respectively (Anton et al, 2008; Johnson, Seneviratne, Wang, Ait-Daoud, & Li, 2013; Kranzler, Armeli, et al, 2014; Kranzler, Covault, et al, 2014; Oslin et al, 2003). There is evidence that SNPs in KCNB1 , KCND2 , KCNJ6 , KCNMA1 , and KCNQ1/5 are associated with alcohol dependence or increased risk for developing an alcohol use disorder (Buhler et al, 2015; Clarke et al, 2011; Edenberg et al, 2010; Kendler et al, 2011; Namkung, Kim, & Park, 2005; Pan et al, 2013; Zuo et al, 2012). This emerging evidence that K + channel transcript levels correlate with drinking and polymorphisms in K + channels are related to alcohol dependence implicate select K + channels that may cause or maintain heavy alcohol intake and may represent a new relevant set of biomarkers for alcohol dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding the K V 2.2 channel protein, KCNB2, was found in a ciseQTL for alcohol consumption, and two SNPs in the KCNB2 gene are associated with maximum number of drinks consumed in 24 h [102]. Additionally, transcript levels of the gene encoding the K V 2.1 chan nel protein, KCNB1, was increased in hippo campus from alcoholic postmortem brain [103], and expression of both KCNB1 and KCNB2 in the superior frontal gyrus were strongly associated with lifetime drinking in alcoholics [78].…”
Section: Preclinical Pharamcogenetic Targets For Treating Alcohol Addmentioning
confidence: 99%
“…L'analyse récente de cohortes américaines confirme l'association de la dépendance à l'alcool avec des variants qui changent des acides aminés des produits des gènes ADH1B et ADH1C [23]. D'autres métaanalyses de GWAS déjà publiées confirment l'implication des gènes que nous venons de décrire, et en identifient de nouveaux ainsi que de nouvelles voies neurobiologiques intervenant dans l'addiction à l'alcool et dans diverses pathologies qui lui sont associées [23,24].…”
Section: Gènes Associés à La Dépendance à L'alcoolunclassified